Helicobacter pylori infection in patients with selective immunoglobulin a deficiency. (31st March 2016) - Magen, E.; Waitman, D.‐A.; Goldstein, N.; Schlesinger, M.; Dickstein, Y.; Kahan, N. R.
Summary: Selective immunoglobulin A (IgA) deficiency (IgAD) is the most common primary immunodeficiency in the western world. The aim of the study was to investigate the prevalence and clinical characteristics of Helicobacter pylori‐ infected dyspeptic patients with IgAD. Case samples were drawn from all subjects ≥ 12 years of age ( n = 104729) who had undergone serum total IgA measurements during 2004–14 for any reason at Leumit Healthcare Services (Israel) and had serum total IgA < 0·07 g/l. The control group was comprised of a random sample of remaining patients with a case–control ratio of 10 controls for each case. The dyspeptic diseases were identified and retrieved from Leumit Health Care Services electronic database using specific ICD‐9‐CM diagnostic codes. The case group included 347 subjects and the control group 3470 subjects. There were no significant differences in the prevalence of patients with dyspepsia [84 (24·2%) versus 821 (23·6%) for cases and controls, respectively]. Additionally, there was no difference in a proportion of dyspeptic H. pylori ‐positive subjects [59 (17·1%) versus 524 (15·1%)] between the case and control groups. Only 59 (17%) among the 347 IgAD patients underwent gastroscopy. A significantly larger proportion of case subjects experienced several forms of gastritis [13 (61·9%) versus 38 (21·6%), P < 0·001), duodenal ulcers [seven (33·3%) versus 19 (10·8%); P = 0·01] and nodular lymphoid hyperplasia (NLH) [two (9·5%) versus none; P = 0·011]. IgAD is not associated with increased prevalence of H. pylori ‐associated dyspepsia; nevertheless, H. pylori ‐infected dyspeptic IgAD subjects experience more EGD‐proved gastritis, duodenal ulcers and NLH.